Turkish – Azerbaijani Falsifications of the Armenian Toponyms as an Indication of the Genocidal Policy - Danielyan, Eduard (ՀՀ ԳԱԱ հրատ.)
Armenia’s more than ten-millennia old historical resources as cognitive factors have an important significance in the national security system. Their essential part is constituted by the Armenian Highland’s toponyms symbolizing the indigenous Armenian Nation’s cultural creation – the backbone of the Armenian statehood having millennia-old ethno-spiritual and civilizational roots as attested by archaeological monuments and architectural relics, petroglyphs and cuneiform inscriptions, anthropological data and other historical sources, as well as results of linguistics research making use of historical comparative1 and glottochronological methods. Հայաստանի ավելի քան տասհազարամյա պատմամշակութային ռեսուրսները, որպես ճանաչողական գործոններ, կարևոր նշանակություն ունեն ազգային անվտանգության համակարգում: Հայկական տեղանունները խորհրդանշում են Հայկական լեռնաշխարհում հայ ազգի տեղաբնիկությունը և մշակութակերտ գործունեությունը՝ էթնո-հոգևոր և քաղաքակրթական արմատներով Հայոց պետականության հիմնասյունը, վկայված հնագիտական և ճարտարապետական հուշարձաններով, ժայռապատկերներով, ինչպես նաև պատմահամեմատական ու լեզվաժամանակագրական մեթոդներով կատարվող լեզվաբանական հետազոտություններով վերհանվող արդյունքներով: Более чем десятитысячелетние исторические ресурсы Армении имеют важное значение в системе национальной безопасности, как познавательные факторы. Их существенную часть составляют армянские топонимы, символизирующие исконность и культурнօ-созидательную деятельность коренного армянского народа на Армянском нагорье, являющуюся стерженем истории Армянской государственности, с ее этно-духовными и цивилизационными корнями, засвидетельствованными археологическими памятниками и результатами лингвистических исследований сравнительно-историческим и глоттохронологическим методами.
Keywords: Political Science; Topology; History